1988
DOI: 10.1111/j.1476-5381.1988.tb11665.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of 1‐methyl‐4‐phenyl‐pyridinium (MPP+) toxicity: incubation of rabbit caudate nucleus slices with MPP+ followed by biochemical and functional analysis

Abstract: 1 Slices of rabbit caudate nucleus were preincubated for up to 24h in vitro in the presence of the neurotoxic compound 1-methyl-4-phenyl-pyridinium (MPP+). Subsequently the levels of endogenous monoamines in the slices were determined by h.p.l.c. with electrochemical detection. MPP +, in concentrations higher than 32 nm significantly diminished the dopamine levels within the slices in a concentration-and time-dependent manner; at 32yM the depletion was more than 95%. The concentration of the major metabolite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, the combination of MPTP and CPP caused a slight reduction in DOPAC and a significant decrease in HVA. The reduction of metabolite concentrations could be related to the fact the MPP + has MAO blocking properties (Feuerstein et al 1988). Taken together, these results indicate that CPP provided no protection against MPTP-induced dopamine depletion in the putamen.…”
Section: Discussionmentioning
confidence: 85%
“…However, the combination of MPTP and CPP caused a slight reduction in DOPAC and a significant decrease in HVA. The reduction of metabolite concentrations could be related to the fact the MPP + has MAO blocking properties (Feuerstein et al 1988). Taken together, these results indicate that CPP provided no protection against MPTP-induced dopamine depletion in the putamen.…”
Section: Discussionmentioning
confidence: 85%
“…For example, hPSC-derived mDA neurons have been used as a model of MPP+ toxicity and GDNF protection (Zeng et al, 2006), but MPP+ toxicity is known to involve the fine terminal arborization of mDA terminals in the striatum, which occur only in the presence of appropriate synaptic targets of mDA neurons as well (Feuerstetin et al, 1988), and thus such studies might be enhanced. Co-cultures of mDA neurons and striatal neurons for use in studies of MPP+ toxicity can be created from rodent fetal material (Koutsilieri et al, 1993), but this allows for similar studies using human material.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of the cellular factor that could facilitate or induce oxidation of dopamine would provide an attractive strategy in the understanding of the pathogenesis of dopaminergic degeneration in PD. MPP + possesses two opposing effects, on one hand it leads to an extensive release of dopamine and on the other hand MPP + inhibits monamine oxidase (MAO)-A (Feuerstein et al 1988 ), with MAO-B only slightly inhibited (Fritz et al 1985 ), thereby counteracting the oxidation of dopamine. A process by which dopamine oxidation still could occur is via COX-2, as COX-2 itself can lead to the generation of ROS (Smith et al 1991 ) and has been shown to react with dopamine to form dopamine-quinone (Teismann et al 2003a ).…”
Section: Discussionmentioning
confidence: 99%